Limnology of tundra ponds, Barrow, Alaska - Hobbie, John E. (Dowden, Hutchinson & Ross, 1980)
This book is a report of investigations of several small ponds on the arctic tundra near Barrow, Alaska. The main study, which ran from 1971 through 1973, was funded from three sources: The National Science Foundation, the State of Alaska through the University of Alaska, and individual companies and members of the petroleum industry. The NSF funding was under the joint sponsorship of the U.S. Arctic Research Program (Division of Polar Programs) and the U.S. International Biological Program (Ecosystem Analysis Program). The U.S. Tundra Biome Program was under the overall direction of Jerry Brown of the U .S. Army Cold Regions Research and Engineering Laboratory and consisted of aquatic and terrestrial sections.